Outstanding of learning Based on Using Historical Sites Colonial in Ternate City as a Source of Learning - Gazali Far Far (Universitas Muhammadiyah Mataram, 2020)
Teaching and learning activities (learning), especially the subjects of history, the focus or object of their discussion about human activities (events) that are relevant to the past with their evidence based on space and time. So to explain past events with current conditions, presumably separating problems in the implementation of learning. With the classical learning method (lecture method) and learning that is always carried out in the classroom, so that it affects the interest and activeness of students in participating in learning history. So it is not surprising that stigmatization appears that history lessons seem very boring. Therefore, hopefully with this writing, it can be a solution in learning history by utilizing local historical relics as a source of learning or other activities that contain educational value. In this article, outlining and presenting examples of how to use colonial heritage buildings in the city of Ternate as a source of learning. Because it is necessary to know that, the existence of historic buildings (fortresses) with a large number in the city of Ternate. So it is very effective if the existing potential can be used as a source of learning with the Outdoor Study approach. In addition, this article also explains the steps of outdoor study-based learning in utilizing historical relics as learning resources.